(3cJGH GdefJNH ef QSGFd GdbGVi GdCLd GdQFjSs - (3YR GdOjf YHO GdMejO Hf GdMSjf Hf YJjb Hf QTjbs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdabjQ Edi QMeI QHg JYGdi YHO GdMejO Hf GdMSjf Hf YJjb dhdG hCeQc GdWGYI eG CNd GdNdb YfOi s
(3BNQgG (B:s
(3abO YbOJ eG MjjJ hGKHJ GdcJGH Ydi YbOi HNW jOi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs